Toll-like receptor 1 locus re-examined in a genome-wide association study update on anti-helicobacter pylori IgG titers - Lam, Suk Yee; Mommersteeg, Michiel C.; Yu, Bingting; Broer, Linda; Spaander, Manon C. W.; Frost, Fabian; Weiss, Stefan; Völzke, Henry; Lerch, Markus M.; Schöttker, Ben; Zhang, Yan; Stocker, Hannah; et al. (Gastroenterology, 2022)
Background & Aims - A genome-wide significant association between anti-Helicobacter pylori (H pylori) IgG titers and Toll-like receptor (TLR1/6/10) locus on 4p14 was demonstrated for individuals of European ancestry, but not uniformly replicated. We re-investigated this association in an updated genome-wide association study (GWAS) meta-analysis for populations with low gastric cancer incidence, address potential causes of cohort heterogeneity, and explore functional implications of genetic variation at the TLR1/6/10 locus. - Methods - The dichotomous GWAS (25% individuals exhibiting highest anti-H pylori IgG titers vs remaining 75%) included discovery and replication sampls of, respectively, n = 15,685 and n = 9676, all of European ancestry. Longitudinal analysis of serologic data was performed on H pylori-eradicated subjects (n = 132) and patients under surveillance for premalignant gastric lesions (n = 107). TLR1/6/10 surface expression, TLR1 mRNA, and cytokine levels were measured in leukocyte subsets of healthy subjects (n = 26) genotyped for TLR1/6/10 variants. - Results - The association of the TLR1/6/10 locus with anti-H pylori IgG titers (rs12233670; β = −0.267 ± SE 0.034; P = 4.42 × 10−15) presented with high heterogeneity and failed replication. Anti-H pylori IgG titers declined within 2-4 years after eradication treatment (P = 0.004), and decreased over time in patients with premalignant gastric lesions (P < 0.001). Variation at the TLR1/6/10 locus affected TLR1-mediated cytokine production and TLR1 surface expression on monocytes (P = 0.016) and neutrophils (P = 0.030), but not mRNA levels. - Conclusions - The association between anti-H pylori IgG titers and TLR1/6/10 locus was not replicated across cohorts, possibly owing to dependency of anti-H pylori IgG titers on therapy, clearance, and antibody decay. H pylori-mediated immune cell activation is partly mediated via TLR1 signaling, which in turn is affected by genetic variation.
Gesehen am 13.02.2023